Design and finite element analysis of an extractor machine for castor oil biodiesel production - Linus Adache Adache; Taye Stephen Mogaji; Mohammed Olabanji Olayinka; Zephaniah Ayodeji Olagoke (Journal of Applied Research in Technology & Engineering)
This research presents the design of a castor oil extractor for producing castor oil biodiesel. The machine was designed using appropriate design equations in the design analysis of the machine, and finite element analysis was conducted to determine the structural integrity, functionality and manufacturability of the system. With a total load distribution of 729 kN resulting from the screw shaft and the weight of other accessories, the behaviour of the frame material under different loading conditions was stated. Solidworks/Ansys analysis of the screw shaft showed a maximum stress distribution of 0.52599 MPa, which is below the yield strength of 460 MPa for the material used. The maximum deformation under loading conditions is 0.00042373 mm, which is negligible and does not pose a risk of failure of the machine. The fabrication was done using locally available materials. The performance of the developed machine was evaluated using castor seed and obtained output capacity of 120.2 kg/h and extraction efficiency of 58% respectively at a speed of 30 rpm. The machine can function independently for extracting castor oil and can also be used to extract oil from other seeds of similar sizes as castor seed, thereby minimizing challenges associated with conventional extracting machines.